Quantitative Expression of TYR, CD34, and CALD1 Discriminates Between Canine Oral Malignant Melanomas and Soft Tissue Sarcomas - Mayra F. Tsoi; Tuddow Thaiwong; Rebecca C. Smedley; Erica Noland; Erica Noland; Matti Kiupel; Matti Kiupel (Frontiers in Veterinary Science, 2021)
Canine oral malignant melanomas (OMMs) exhibit a variety of morphologic phenotypes, including a spindloid variant. The microscopic diagnosis of spindloid OMMs is based on junctional activity and/or the presence of melanin pigment. In the absence of these features, spindloid OMMs are difficult to differentiate from soft tissue sarcomas (STS). An antibody cocktail (MDX) that includes Melan-A, PNL2, and tyrosinase-related proteins 1 and 2 (TRP-1 and TRP-2) is the current gold standard for identifying amelanotic OMMs by immunohistochemistry (IHC). However, MDX is less sensitive for diagnosing spindloid amelanotic OMMs. This raises concern for biopsy specimens that lack overlying epithelium, making it potentially difficult to differentiate OMM from STS by IHC. The goal of this study was to identify additional markers to help differentiate between STS and OMMs that lack pigment and junctional activity. SOX-10 has recently been proposed as a sensitive marker for melanocytes in humans but has not been validated in dogs. Similarly, RNA expression for various genes has been analyzed in humans, but not in the context of diagnosing canine melanocytic neoplasms. For this retrospective study, formalin-fixed, paraffin-embedded tissues from 20 OMMs, 20 STS, and 20 oral spindle cell tumors (OSCTs) that lacked junctional activity and pigmentation were selected. IHC for MDX, SOX-10, and laminin, in parallel with RT-qPCR of TYR, SOX10, CALD1, CD34, DES, and LAMA1, was performed in all cases. TYR, CD34, and CALD1 were the most discriminatory genes in differentiating between OMM and STS, all having 100% specificity and 65, 95, and 60% sensitivity, respectively. While all 20 OMMs were immunohistochemically labeled for SOX-10, two STS were also labeled (100% sensitivity and 90% specificity). MDX IHC labeled all 20 OMMs and no STS. Surprisingly, none of the 20 OSCTs expressed TYR RNA above the cutoff, and 14/20 OSCTs expressed CALD1 or CD34 RNA above the cutoff, thereby confirming them as STS. Four OSCT were suspect STS, and no OSCTs were confirmed as OMMs based on IHC and RNA expression patterns. In conclusion, the RNA levels of TYR, CD34, and CALD1 should be evaluated in suspected amelanotic OMMs that are negative for MDX to accurately differentiate between OMM and STS.